2016
DOI: 10.1177/0162353216640936
|View full text |Cite
|
Sign up to set email alerts
|

Finnish Teachers’ Conceptions of Giftedness

Abstract: This article presents two independent studies of Finnish teachers' conceptions of giftedness and considers whether it is a malleable or fixed quality. The first qualitative study examined elementary school teachers' (N = 212) conceptions via inductiveoriented content analysis, whereas the second study measured teachers' (elementary n = 184, secondary n = 279) conceptions with a quantitative approach. According to teachers' open-ended definitions, giftedness was seen to be multidimensional and a characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 41 publications
1
46
0
3
Order By: Relevance
“…In day-to-day work, the promotional and the restrictive seem to be regularly intertwined (Kärkkäinen, 2011). Studies of Finnish teachers' implicit theories show that teachers mainly have an incremental theory of giftedness (Laine, Kuusisto, & Tirri, 2016). Furthermore, Finnish teachers seem to regard the academic competence of poorly achieving students as malleable, but have more fixed views of the stability of high-achievers' competence (Kärkkäinen, 2011;Kärkkäinen & Räty, 2010).…”
Section: Finnish Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In day-to-day work, the promotional and the restrictive seem to be regularly intertwined (Kärkkäinen, 2011). Studies of Finnish teachers' implicit theories show that teachers mainly have an incremental theory of giftedness (Laine, Kuusisto, & Tirri, 2016). Furthermore, Finnish teachers seem to regard the academic competence of poorly achieving students as malleable, but have more fixed views of the stability of high-achievers' competence (Kärkkäinen, 2011;Kärkkäinen & Räty, 2010).…”
Section: Finnish Contextmentioning
confidence: 99%
“…These four teachers were chosen from a survey measuring Finnish teachers' (N = 463) implicit theories using Carol Dweck's mindset inventory (Dweck, 2000(Dweck, , 2006Laine et al, 2016). The sample item for the scale was 'Your giftedness is something very basic about you that you can't change very much. '…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…Still, there has been little research on implicit beliefs about giftedness (cf. [23,24]) compared to implicit beliefs about intelligence. The intriguing questions are whether the nature of these concepts is seen in a similar way and whether these views have similar effects on achievement.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that giftedness might be seen as more fixed in nature than intelligence. In their study, Laine et al [24] examined Finnish teachers' implicit beliefs about giftedness. The results indicated that most of the teachers ( = 463) had a growth mindset about giftedness (54%), one-third (30%) had a fixed mindset, and the rest (16%) had a mixed mindset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation